THE USE OF DIOCTAHEDRIC SMECTITIS IN THE COMPLEX THERAPY OF INFANTILE ATOPIC DERMATITIS - A.A. Alexeeva; L.S. Namazova-Baranova; R.M. Torshkhoeva; E.A. Vishneva; Yu.G. Levina; N.I. Voznesenskaya ("Paediatrician" Publishers LLC, 2011)
Among pediatric allergic diseases, atopic dermatitis takes one of the leading positions. Functionality of gastro-intestinal tract plays quite an important role in its development. Gastro-intestinal lesions first of all lead to the damage of protective mucosal barrier thus leading to the damage of intestinal barrier function. Due to this, therapy aimed at allergen and toxin elimination plays an important part in complex treatment of atopic treatment. The most effective are sorption methods. In pediatric atopic dermatitis guidelines enterosorbents are included along with elimination diet, local treatment and antihistamines. In the recent years dioctahedric smectitis (Neosmectin)  is in quite active use. This article contains results of the research upon its use in complex treatment of atopic dermatitis in children. Key words: atopic dermatitis, dioctahedric smectitis, children. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 93-97.)